EFFECT OF ION IMPLANTATION ON THE COMPOSITION, STRUCTURE AND OPTICAL PROPERTIES OF SILICON - Mustafoeva , Nodira Moyliyevna; Mustafaeva , Nilufar Moyli Qizi (Educational Research in Universal Sciences, 2023)
In this work, comparative studies of the effect of bombardment with Ar+ and Ni+ ions on the composition, structure, and light transmission coefficient of single-crystal Si are carried out. In both cases, implantation leads to disordering of the surface layers and a decrease in K. After heating at T = 900 K of Si implanted with Ni+ ions, epitaxial phases are formed in the surface region of Si, depending on the dose of ions (at D < 51015 см-2) and films (at D = 61016 см-2) NiSi2.